Operation Optimization of Microgrid System Based on Intelligent System Model - Jian Kang (Advances in Multimedia)
In order to improve the operation optimization effect of the microgrid system, this paper combines the intelligent system model to construct the operation optimization model of the microgrid system. Moreover, this paper conducts a quantitative calculation and research on the maximum compensation capacity of the active power filter device and proposes a harmonic power adaptive compensation control strategy in the case of the limited output capacity of the APF device. In addition, this paper adopts the method of extracting the harmonic current command in the synchronous coordinate system based on the band-pass filter composed of SOGI and combines the RDFT algorithm to determine the number of harmonics that can be compensated and the degree of compensation for the harmonic number. Finally, this paper combines simulation experiments and comprehensive evaluation to study and verify that the operation optimization effect of the microgrid system based on the intelligent system model is better and can effectively improve the operation effect of the microgrid system.